Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.20897/ejosdr/81642
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of Waste Castor Seed Cake: A Thermo-Kinetics Study

Abstract: Biomass pyrolysis is a thermo-chemical conversion process that is of both industrial and ecological importance. The efficient chemical transformation of waste biomass to numerous products via pyrolysis reactions depends on process kinetic rates; hence the need for kinetic models to best design and operate the pyrolysis. Also, for an efficient design of an environmentally sustainable pyrolysis process of a specific lignocellulosic waste, a proper understanding of its thermo-kinetic behavior is imperative. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Pérez et al (2012), reported that E α values from the KAS method became larger than those from the Friedman method for α >0.65. In other literature (Sokoto and Bhaskar, 2018), the activation energy calculated using the Friedman method decreased with increasing α in the range 0.1-0.6, while the values derived from the KAS method were stable for α values of 0.1-0.15 and 0.2-0.4. A decrease in E α values was observed for α values of 0.4-0.6.…”
Section: Calculation Of Activation Energymentioning
confidence: 67%
“…Pérez et al (2012), reported that E α values from the KAS method became larger than those from the Friedman method for α >0.65. In other literature (Sokoto and Bhaskar, 2018), the activation energy calculated using the Friedman method decreased with increasing α in the range 0.1-0.6, while the values derived from the KAS method were stable for α values of 0.1-0.15 and 0.2-0.4. A decrease in E α values was observed for α values of 0.4-0.6.…”
Section: Calculation Of Activation Energymentioning
confidence: 67%
“…This temperature range is characterized by a large release of low molecular weight volatile matter. This is the most active region of pyrolysis, where thermal decomposition of hemicellulose, cellulose, extractive substances, and part of lignin occur (Ceylan & Topçu, 2014;Sokoto & Bhaskar, 2018). The loss of mass in the pyrolysis region was lower in the PDS sample, because the oil and other substances soluble in non-polar solvents were removed during the oil extraction process (White, 1987).…”
Section: Fuel Propertiesmentioning
confidence: 99%